A constituição e a implantação dos Institutos Federais no contexto da expansão do Ensino Superior no Brasil: o caso do IFC – Campus Rio do Sul - Tavares, Moacir Gubert (2014)
This work broaches the process of creation and implantation of Federal Institutes of Education, Science and Technology (FIs) as an integral part of educational policies faced to the expansion of the Higher Level Education in Brazil, during the period of 2003-2012. Besides theoretical studies related to the literature revision and analysis of documents, the present research availed of empirical data obtained from a case study accomplished in Federal Institute Catarinense – Campus Rio do Sul, which were submitted a qualitative analysis. The questions that led the elaboration of this thesis express of the following way: if the federal government intended to contribute to the enlargement of the vacancies in the public segment of the Higher Level Educational – especially of the teacher formation courses – without to give up of the connection between research and extension, because it chose to trust this mission to the newly-created Federal Institutes, contrary to keep it under the responsibility of the federal universities, that are reference in the attendance of this kind of request? The present thesis considers the presupposed that, in face of the difficulties that the capital system has found to do with the federal universities resign to their demands more immediate, the re-structuration of the Federal Network manifests itself in the effectivity of an alternated institutional pattern, based on the expectancy of that the Federal Institutions could adapt themselves more easily to these requests. This investigation has as general purpose to analysis the creation and the implantation of Federal Institute Catarinense – Campus Rio do Sul, with the intent to verify the features of this new institutional identity, especially in that it refers to the triad teaching-researching-extension and the links established with the clusters. The particular objectives are as follows: to make explicit what were the characteristics that determined the institutional identity of the old Federal Agrotechnical School of Rio do Sul and the type of linking that this Institution established with the activities of researching and extension; to identify, from the analysis of empirical data, the elements that express the particular forms that the process of “ifetização” assumed in the case of FIC – Campus Rio do Sul, especially those that bond to the attendance of the requests of the clusters and the articulation between the activities of teaching, researching and extension; to analysis the documents that regulated and directed the process of conception and creation of Federal Institutes; to make evident the results of the theses and dissertations about Federal Institutes and the expansion of the Higher Level Educational in Brazil, in order to make explicit the aspects that happen again and turning them universal in more extensive context of these policies; to carry out a historic survey of the genesis and the development of the integral institutions of the Federal Network, as well as of Brazilian universities, so as to identify the similarities and differences that established between these institutions of education, especially in that refers its social function and in the degree of the autonomy that they present in respect to the immediate interests of the capital. This investigation is directed from Marxist epistemological perspective, articulating elements of Marx and Gramsci’s works to the examination of the object investigated.